Comparison of Different Finite Element Method on Cracked Cantilever Beam Modal Analysis - Asmawi, Rosli; Luyoh, Irvine Kulleh (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Finite Element Analysis or Simulation software have been used widely in the world of engineering. Can different party transfer or share information with different software? In this study, a software comparison is being conducted. The study is on studying the presence of crack in a cantilever beam. The previous study uses ABAQUS as Finite Element Analysis software. For this study, ANSYS will be used for Finite Element Analysis software. Any structure with a crack is vulnerable to failure, depending on the mode of vibration. Failure is caused by the superposition of the frequency of the periodic force acting on the structure and the natural frequency of the structure. It is critical to determine the natural frequency to be aware of resonance caused by the periodic load. The natural frequency and mode shapes of transverse vibration for both un-cracked and cracked cantilever beams were extracted in this modal analysis study for the first three modes. For cracked beams, various crack depths, crack opening, and crack locations are analyzed. In this study, it was discovered that the presence of a crack reduces the natural frequency. The amount of reduction varies depending on the location, depth, and size of the crack opening. After the data has been extracted for ANSYS, it will be compared with the data obtained from previous studies which use ABAQUS. It is found that despite a slight percentage discrepancy, both data collected share the same trend.